Features of Financial and Legal Incentives of Investment Activities in the Regions - POPADYUK, Nikita K.; PANINA, Olga V.; EREMIN, Sergey G.; GALKIN, Andrey I.; SAVELYEV, Alexander A. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).26, 2018)
Research of features of financial and legal incentives of investment activities in the regions. Methodological basis of the study raised issues were the following: general scientific methods of cognition generalization, analogy, analysis and synthesis, elaboration, comparison, logical method, etc. Conducted interdisciplinary analysis of literature and sources on stimulating investment activities, with particular emphasis given to the Institute financial and legal incentives. Formed the author's definition of the term ʼfinancial and legal stimulus of investment activity of regionsʼ. Studied types of financial and legal incentives of investment activities of the regions. Analyzed regional legislation and judicial practice on the subject of study places financial incentives in the legal field of regional legislation. Identified conflicts in the system of financial and legal incentives of investment activities of the regions. A proposal to optimize the preliminary control of the Prosecutor's offices of the legality of the investment legislation, in particular, the structure of which has different financial and legal incentives of investment activities in Russian regions.